The answer is
![x = \frac{-7+ \sqrt{193} }{4}](https://tex.z-dn.net/?f=x%20%3D%20%20%5Cfrac%7B-7%2B%20%5Csqrt%7B193%7D%20%7D%7B4%7D%20)
.
There is very similar question on Brainly, in which dimensions of the living room are given (20 feet, 30 feet).
So, knowing this, we first need to calculate how much 6% of the living room is.
The area of the living room is 600 square feet, since it is rectangle-shaped:
P = a * b = 200 feet * 30 feet = 600 square feet.
6% of 600 square feet is 36 square feet:
600 square feet : 100% = A : 6%
A = 600 * 6 / 100 = 36 square feet
The area of the triangular-based cabinet (A) is
![A = \frac{a*h}{2}](https://tex.z-dn.net/?f=%20A%20%3D%20%5Cfrac%7Ba%2Ah%7D%7B2%7D%20)
, where a is the base, and h is the height of the triangle.
It is given:
A = 36
a = 2x + 3
h = 3x + 6
Now, let's implement this to the formula
![A = \frac{a*h}{2}](https://tex.z-dn.net/?f=A%20%3D%20%20%5Cfrac%7Ba%2Ah%7D%7B2%7D%20)
:
![36 = \frac{(2x+3)(3x+6)}{2}](https://tex.z-dn.net/?f=36%20%3D%20%20%5Cfrac%7B%282x%2B3%29%283x%2B6%29%7D%7B2%7D%20)
⇒
![36*2=6 x^{2} +12x+9x+18](https://tex.z-dn.net/?f=36%2A2%3D6%20x%5E%7B2%7D%20%2B12x%2B9x%2B18)
![72=6 x^{2} +21x+18](https://tex.z-dn.net/?f=72%3D6%20x%5E%7B2%7D%20%2B21x%2B18)
Let's both sides divide by 3:
![24=2 x^{2} +7x+6](https://tex.z-dn.net/?f=24%3D2%20x%5E%7B2%7D%20%2B7x%2B6)
⇒
![2 x^{2} +7x-18=0](https://tex.z-dn.net/?f=2%20x%5E%7B2%7D%20%2B7x-18%3D0)
This is the quadratic formula (
![a x^{2} +bx+c=0](https://tex.z-dn.net/?f=a%20x%5E%7B2%7D%20%2Bbx%2Bc%3D0)
) for which
![x = \frac{-b+\sqrt{b^{2} -4ac} }{2a}](https://tex.z-dn.net/?f=x%20%3D%20%20%5Cfrac%7B-b%2B%5Csqrt%7Bb%5E%7B2%7D%20-4ac%7D%20%7D%7B2a%7D%20)
or
<span>
![x = \frac{-b-\sqrt{b^{2} -4ac} }{2a}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-b-%5Csqrt%7Bb%5E%7B2%7D%20-4ac%7D%20%7D%7B2a%7D%20)
.
</span>We will use only <span>
![x = \frac{-b+\sqrt{b^{2} -4ac} }{2a}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-b%2B%5Csqrt%7Bb%5E%7B2%7D%20-4ac%7D%20%7D%7B2a%7D%20)
, because the length cannot have negative value.</span>
<span>From the equation
![2 x^{2} +7x-18=0](https://tex.z-dn.net/?f=2%20x%5E%7B2%7D%20%2B7x-18%3D0)
, we know that
</span>a = 2
b = 7
c = -18
Thus, <span>
![x = \frac{-7+ \sqrt{193} }{4}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-7%2B%20%5Csqrt%7B193%7D%20%7D%7B4%7D%20)
:
</span>